Las casas del Onganiato : política habitacional y sectores populares - Gabriela Gomes (Nuevo mundo - Mundos Nuevos, 2017)
This paper analyzes social intervention from State in housing policies during “Argentine Revolution”. We focus on policies to popular sectors that were promoted by Secretary of Housing, which depended on Social Welfare Ministry, as well as technical and business actors who benefited from social housing. Our object of interest is the main diagnoses and partial solutions aimed to solve housing shortage from Buenos Aires´s metropolitan area.